A Study on the English Standardized Translation of Special Local Products - Yang, Xiaoyan (Journal of Social Science and Humanities, 2025)
In the context of the in-depth advancement of economic development, the export trade of Nanchang’s special local commodities has shown significant growth. In order to help these products better integrate into the international market, it has become imperative to improve the quality of their English translation quality, in which the importance of standardized translation work is increasingly prominent. This study focuses on the standardization of English translation of Nanchang’s special products, deeply analyzes the existing problems and their causes, and proposes corresponding optimization solutions based on this, aiming to provide useful ideas and practical references for the international language services of Chinese special local products.